Microprogramme en pédagogie de l’enseignement supérieur pour les enseignants : incidences sur la motivation et les stratégies d’apprentissage des étudiants - Mélanie Cabana; Denis Bédard (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
Since 2009, more and more teachers at the Université de Sherbrooke and from other insitutions have been asking for the training offered by the Microprogramme en pédagogie de l’enseignement supérieur, during which they are invited to immerse themselves in a reflective process centered on student learning. What are the impacts of this “long term” program? The purpose of this study is to verify the impact of this training program on the motivation and learning strategies of the students of teachers who received this training. Perceptual data collected from 252 students from diverse disciplinary backgrounds enrolled in six programs (enseignement préscolaire et primaire, enseignement collégial, politiques appliquées, chimie, informatique et génie) shows that teachers trained in higher education pedagogy offered lectures and activities that helped keep their students motivated throughout the semester. More specifically, the data reveal that teachers coming from the programs “enseignement préscolaire et primaire”, as well as “enseignement au collegial” have also used active learning that supports the development of contextualization, information selection and monitoring strategies in their students.